Is there financial accelerator in indonesian banking? - Dadang Lesmana; Felisitas Defung; Wirasmi Wardhani (Jurnal Keuangan dan Perbankan, 2022)
The purpose of this study is to examine the effect of the business cycle on price-cost margins in Indonesian banking. The research method used is the System Generalized Method Moment (SYS-GMM) to analyze 94 conventional banks in Indonesia for the period 2011-2020. The results of this study indicate that the business cycle has two effects on the price-cost margin in Indonesian banking. First, GDP has no effect on the price-cost margin. Second, credit has a negative effect on price-cost margins in Indonesian banks. Our result study is to prove the results of research on "financial accelerators" in previous studies. This study suggests banks and policymakers in Indonesia must be able to assist the economy in providing credit to accelerate economic recovery, which can reduce the default risk.